Incidence of triple receptor status (ER, PR, HER-2) in patients undergoing mastectomy in MMC and RGGGH, Chennai, India during 2010-2014: a prospective and retrospective study - Subramanian, P.; Venkateswaran, P. (International Surgery Journal, 2018)
Background: Breast cancer is the most common of all cancers and is the leading cause of cancer deaths in women worldwide, accounting for about 1.5% of all deaths. A recent study in India revealed that 1 in 28 women develop breast cancer during their lifetime. Objective was to study the incidence of receptor status in patients who underwent mastectomy for carcinoma breast in Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai, India. Methods: All women with carcinoma breast who had undergone a mastectomy in Rajiv Gandhi Government General Hospital in the past 5 years and their resected specimen tested for receptor status by pathologists. Estrogen receptor, Progesterone receptor, Her2/neu receptor by using special kits. Results: The most common type was found to be ER+ PR- Her2- and the least common was the Triple Positive type. Estrogen Receptor alone was positive in 63 patients. It was common for age groups 41-50 years and 31-40 years. Progesterone Receptor alone was positive in 17 patients. It was seen in age groups 51-60 years, 31-40 years, and 41-50 yrs. Her2 neu receptor alone was positive in 20 cases. It was most common in the age group 31-40 years (50% cases). Both ER and Her2/neu receptor were positive in 20 patients. The highest was among the age groups 41-50 years (35%) & 31-40 years (30%). All the three receptors were found to be positive in 8 cases with the highest being in the age group 41-50 years (4 cases) followed by 31-40 years (3 cases) and 51-60 years (1 case). Conclusions: The incidence of Progesterone receptor positivity was 32.5%. It was higher in postmenopausal women (36.25%) compared to premenopausal women (30%).The incidence of Her2/neu receptor positivity was found to be 32.5%. It was equally distributed in premenopausal and postmenopausal women (32.5%). The most common receptor subtype was ER+ve, PR-ve, Her2/neu-ve contributing 31.5%.